A Project study on Philippine Airlines (M&E Dept.) - Wah, Lee Shew.; Salmon, Edwin M.; Quevedo, Francispito; Ramos, Christopher (Diliman, Quezon City College of Engineering, 1986)
The group has chosen the Maintenance and Engineering Department (M&E) of Philippine Airlines as its system for study. The study will cover only the aspects of M&E that deal with the repairs and maintenance of the company's international aircraft. The group shall employ the systems methodology as its approach to the study of the system, with M&E as its system of concern and PAL's Operations Group as the larger system. The objective of the Operations Group is to handle all aspects of aircraft operations (maintenance, flights etc.) at the most efficient and cost saving method. the objective of M&E is to handle the repairs and maintenance of the company's aircraft to provide 100% reliability in aircraft performance and airworthiness. M&E is composed of four main divisions. They are: Line Maintenance, Base Maintenance, Maintenance Support, and Quality Assurance. Each division have their respective sub-divisions. The important aspects of each division have their respective sub-divions. The important aspects of each division have been covered. For Line Maintenance (LM), the study focused on the operations of Line Maintenance International (LMI). For Base Maintenance (BM), we focused on its Shop Services Division (SSD) and its Aircraft Overhaul Division (AOD). For Maintenance Support (MS), we covered the Materials Planning Division (MPD) . Quality Assurance (QA) was also taken into consideration, however, only its relationship and relevance to the whole system have been touched. Each of these subdivisions (LMI, SSD, AOD, MPD, QC, QI) have been looked into in detail, their procedures documented and analyzed. To evaluate their present status, measures of performance for each division and their subdivisions have been established. Performance was measured in terms of meeting specified confidence levels, certain frequency limits and tolerance limits. Essentially,both LM and BM have the same measures of performance since both divisions are closely related and works are done at the same time. They both have the same conditions and constraints. So whatever is the trouble in one is also the trouble in the other. The evaluation yielded the following results: 1. QA is working up to par, 2. AOD is incurring considerable expenses due to overtime thus hampering its performance in terms of efficiency, therefore it is a trouble spot, 3.SSD is working up to par, 4. LMI is suffering from the same problems as AOD, 5. MPD is working up to par if we consider the planning and flow of materials, however, in terms of inventory, they have too much dead inventory. This is not a healthy sign. We shall now consider the trouble spots. For the last year, AOD incurred P1073337 in overtime expenses and its projected overtime expenses for March to December this year is P632,567. The man-hours consumed for overtime last year amounted to 81,067.75 and its projection this year amounts to 47,777. AOD has exceeded the overtime limit of 12 hrs/man/month. For MPD, we discovered the presence of 750,000.00 dead inventory, this is due to obsolescence of aircraft. Due to limited time constraints, the group has decided to concentrate on the problem in AOD since this also affect the performance of LMI and is considered a major problem also by the company. in the AOD, we traced the cause of the problem to poor manpower scheduling, uneven workload, shorter working time, uneven manpower distribution and insufficient supervision. These consequently result in higher labor costs and delays in the scheduling of other workloads. As a solution to this, the group developed three manpower scheduling models which schedules the manpower according to the weekly workload, after which the manpower is leveled according to management policies. Furthermore, the group recommends the following: 1. The addition of a third shift (originally 2 shifts only) to stagger workload, 2. Base the schedule entirely on the manpower requirements determined by the workload to eliminate overtime, 3. redistribute the workload to prevent unequal distribution of workload and consequently manpower distribution.
IE 151
Feasibility study
Keywords: Philippine Airlines; Airlines; Production engineering